Safe Tractor Operations: More Tractor Safety Tips: AE603, 6/2024 - Gorucu, Serap; Lehtola, Carol J.; Brown, Charles M. (EDIS, 2024)
This publication from the Safe Tractor Operations series discusses tips for maneuvering tractors, hazards of filling gas cans, hand signals, handling large hay bales, and more. Written by Serap Gorucu, Carol J. Lehtola, and Charles M. Brown, and published by the UF/IFAS Department of Agricultural and Biological Engineering, June 2024.